Elasticity of Swollen and Folded Polyacrylamide Hydrogel Using the MARTINI Coarse-Grained Model - Rho, Seunghyok; Koh, Heeyuen; Yu, Ji Woong; Koo, Hye Been; Kim, Sebin; Jung, Je Yeon; Jung, Eun Yeong; Nam, Chongyong; Lee, Jae Young; Jeon, Kyounghwa; Chang, Jae Byum; Kim, Do Nyun; et al. (ACS Applied Materials and Interfaces, 2025)
One of the key advantages of using a hydrogel is its superb control over elasticity obtained through variations of constituent polymer and water. The underlying molecular nature of a hydrogel is a fundamental origin of hydrogel mechanics. In this article, we report a Polyacrylamide (PAAm)-based hydrogel model using the MARTINI coarse-grained (CG) force field. The MARTINI hydrogel is molecularly developed through Iterative Boltzmann inversion (IBI) using all-atom molecular dynamics (AAMD), and its quality is evaluated through the experimental realization of the target hydrogel. The developed model offers a mechanically high-fidelity CG hydrogel that can access large-scale water-containing hydrogel behavior, which is difficult to explore through AAMD in practical time. With the modeled hydrogel, we reveal that the polymer conformation modulates the elasticity of the hydrogel from a folded state to a swollen state, confirmed by the Panyukov model. The results provide a robust bridge for linking the polymer conformations and alignment to their bulk deformation, enabling the multifaceted and material-specific predictions required for hydrogel applications.
Keywords: Boltzmann; Boltzmann inversion; Coarse Graining; Coarse-grained force fields; Coarse-grained modeling; Forcefields; Iterative boltzmann iteration; MARTINI force field; Polyacrylamide hydrogels; Polymer conformation; coarse-graining; elasticity; hydrogels; iterative Boltzmann iteration; MARTINI force field; molecular dynamics; polyacrylamide; swelling